Semiotic naturalism in architecture theory - Due, R (International Society for the Philosophy of Architecture, 2017)
This paper seeks to present a kind of skeptical, and, in an indirect way, Wittgensteinian perspective upon purpose and meaning in architecture. The argument presented here revolves around the two notions that, first, there are different categories, which we have available for making architecture seem intelligible to us, and, second, that there are distinct historical discourses in which architecture has been made intelligible in specific ways.